(untitled) (Applied Biological Research, 2019)
The present study was initiated with the objective of marker-assisted introgression of Lr24 and Lr28, wheat leaf rust resistance genes, into an elite susceptible bread wheat genotype MP3299 from NIL-PBW 343. Marker assisted selection alongwith screening of genotypes under epiphytotic conditions was undertaken in this study. SCAR molecular markers SCS73719 and SCS421570 linked to Lr24 and Lr28, respectively, confirmed in segregating population of MP3299 x NIL-PBW 343, were further evaluated for leaf rust resistance under artificial leaf rust condition. In F4 and F5 populations, high degree of leaf rust resistance was observed in plants carrying both Lr24 and Lr28 genes as compared to the plants with individual leaf rust resistance gene Lr24, followed by Lr28. Significant correlation and regression were observed between most of the agronomic traits and coefficient of incidence. Six Lr28 homozygous plants identified with high degree of leaf rust resistance were advanced for yield trials. The identified lines seem potential resistance sources and superior recombinants for future breeding programmes.